Characterization of the process of border suburbs: case of Leticia (Colombia) and Tabatinga (Brasil) (2019)
This article is intended to summarise the research process so-far developed in order to: define, characterise and appropriate concepCaracterización del proceso de conurbación fronteriza: el caso de Leticia (Colombia) y Tabatinga (Brasil) Characterization of the process of border suburbs: case of Leticia (Colombia) and Tabatinga (Brasil) Pablo Enrique Castillo Gutiérrez * * Arquitecto Investigador en Asuntos Amazónicos y docente de la Universidad la Gran Colombia. Correo electrónico: pecg17@gmail.com; pablo.castillo@ugc.edu.co tual elements, which allows one to describe the phenomenon of territorial occupation, from the perspective of sustainability, the Urbanism, the trans-border co-operation, habitability and the Social construction of the Habitat Territorial sustainable; within the framework of multiculturalism, the heritage and the conception of the good life; and the strip of binational border territory, Leticia in Colombia and Tabatinga in the Brazil, located on the Bank of the Amazon River.